Analyzing Grammatical Errors in English Essays by EFL Students - Sharma, Lok Raj (International Research Journal of MMC, 2025)
Error analysis is a systematic scrutiny and elucidation of inaccuracies present in learners' written or spoken expressions due to a lack of their understanding of rules. This study, which executed a cross-sectional research survey design, is to analyze the grammatical errors in a corpus of 105 essays written by 105 BBM (Bachelor of Business Management) and BBA (Bachelor of Business Administration) third semester students studying English as a foreign language (EFL) at Makawanpur Multiple Campus Nepal in the Academic Year 2024. The instrument used for this study to collect data involved students’ written essays in English language. All the students were asked to write an essay of almost 700 words on a topic “Significance of Effective Communication Skills”. Essays of 105 students were selected from those of 143 students through a simple random sampling technique, especially a lottery method. The sample size, which included the essays of 105 students was determined by employing a software calculator, taking a confidence level of 95% and a margin of error of 5%. The study identified 15 sorts of grammatical errors, such as verb tense, article, subject verb agreement, preposition, number agreement, parallelism, word choice, run-on sentence, modifier, fragment, collocation, word order, punctuation, pronoun, and double negative. The results depict that the highest error was in the use of the verb tense (163 occurrences / 14.0%), whereas the lowest error was observed in the use of double negatives (22 occurrences / 2.0%) while writing negative sentences. Mann-Whitney U test (Sig. or p = .846) revealed a uniform distribution of errors across categories of the BBM and BBA programs, ultimately leading to the acceptance of the null hypothesis. The implications of the study extend to language teaching methodologies and assessment practices, aiming to enhance the writing proficiency of EFL learners.